Regulasi Diri Dalam Pembentukan Karakter Integratif Mahasiswa Program Studi PAI di IAIN SAS Babel - Hilhamsyah Hilhamsyah (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2023)
This research is based on the fact that each student has different levels of self-regulation, which means that their level of character also varies. This research is a qualitative descriptive study with the aim of describing student self-regulation in the formation of integrative character in the PAI study program. This research provides a results report by describing and explaining the data obtained regarding student self-regulation in the formation of integrative character in the PAI study program. The research location was at IAIN SAS Babel, and the source of data obtained was the head of the PAI study program and 8 PAI study program students were the research subjects. In this research, data collection methods used structured interviews, structured observation, and documentation. Meanwhile, the data analysis method uses data reduced from interview guides, observations and conclusions based on the facts found. The results of the research show that PAI study program students at IAIN SAS Babel have an integrative character. First, student self-regulation, namely through patterns of receiving, evaluating, searching, formulating, implementing, and assessing. Second, students' integrative character is formed from habits, moral knowing, moral feeling and loving, example and self-introspection.Â Keywords: Self-Regulation, Character, Students